Pengembangan Bisnis Pada Home Industry Kue Kering "Rose Cookies" Menggunakan Business Model Canvas - Aisyah Cindy Sabila; Yusleli Herawati; Marieska Lupikawaty (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
The business model has an important character in influencing the ability of the business to increase competition and predetermined business targets. One tool or business model that can be used successfully is the Business Model Canvas (BMC) which focuses on business concepts in realizing business value. This study analyzes the business model used in the Rose Cookies Home Industry and the problems experienced by the home industry when sales fluctuate due to distribution that only relies on Facebook social media and the financial structure is not detailed. The purpose of this research is to grow the home industry of pastries. The method applied in the following research is descriptive qualitative with data collection techniques through direct interviews with home industry entrepreneurs. The results of the following research are evaluating the 9 elements of the Business Model Canvas to increase market activity and financing structures in the cookie home industry. It is hoped that this research can be useful for increasing revenue streams and growing businesses so they can compete in the future. Keywords: Business Model Canvas, Home Industry, Pastry